Epitope Specificity of Factor VIII Inhibitor Antibodies - Scandella, Dorothea (Hämostaseologie, 1998)
Antibodies that inactivate factor VIII develop most frequently in patients with severe hemophilia A, and they present a serious complication in the therapy of such individuals. Most patients with inhibitors have two or more different antibodies capable of factor VIII inactivation in their plasma, as shown by assays in which several factor VIII domain fragments are tested for neutralization of the inhibitor activity. Such neutralization assays of 23 patient plasmas suggest that there are three common epitopes. These epitopes have been localized by several methods to the A2, A3, and C2 factor VIII domains. Less common inhibitor epitopes lie within the heavy chain acidic region residues 336-372 and in a second region of the C2 domain. The light chain acidic region, residues 1649-1689, may also contain an inhibitor epitope, but this remains to be confirmed. The inhibitor epitopes of autoantibody patients are more restricted as half of them have anti-C2 domain antibodies that make up 95% of the inhibitor activity. The remainder have several inhibitors similar to those of the hemophiliacs. The predominant C2 domain epitope specificity was also seen in rare cases of inhibitor development due to two heat pasteurized factor VIII concentrates in previously treated patients without inhibitors. Inhibitors in mild hemophiliacs are rare as these individuals are usually tolerant to factor VIII. When tolerance is overcome in such patients, the immune responses characterized were diverse. In some patients there was a complete loss of tolerance.
Keywords: Hemophilia A; inhibitor antibodies; epitope mapping